2020
DOI: 10.25115/ejrep.v18i52.3346
|View full text |Cite
|
Sign up to set email alerts
|

Adicciones a internet y funciones ejecutivas en estudiantes universitarios: una revisión sistemática

Abstract: La adicción a internet es un problema de salud pública cada vez mayor, y los estudiantes universitarios reúnen una serie de características que les convierte en población de riesgo.  Numerosos estudios sugieren una relación entre adicciones y alteración en las funciones ejecutivas. Se presenta una revisión bibliográfica que tiene por objetivo identificar variables neuropsicológicas de riesgo para el desarrollo de la adicción a las diferentes aplicaciones de la web en la etapa universitaria. Se realizó una búsq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Although there are numerous studies related to problematic Internet use, there is little empirical research based on studying the relationship between problematic use and executive functions [16]. Despite this, some studies have established a relationship between problematic Internet use and the presence of a deficit in inhibitory control, especially in relation to online gaming addiction [5,6,17]. In other words, a significant relationship has been observed between problematic Internet use, highlighting deficient self-regulation due to compulsive Internet use, and inhibition, establishing that the greater the daily use of the Internet, the lesser the capacity to manage inhibitory control [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are numerous studies related to problematic Internet use, there is little empirical research based on studying the relationship between problematic use and executive functions [16]. Despite this, some studies have established a relationship between problematic Internet use and the presence of a deficit in inhibitory control, especially in relation to online gaming addiction [5,6,17]. In other words, a significant relationship has been observed between problematic Internet use, highlighting deficient self-regulation due to compulsive Internet use, and inhibition, establishing that the greater the daily use of the Internet, the lesser the capacity to manage inhibitory control [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…University students are the most at-risk group in terms of problematic Internet use [10] with six out of every one hundred university students experiencing problems with Internet use [28]. Brotóns et al found that university students constituted a population at risk of problematic Internet use, due to the presence of a series of characteristics, the most notable being the justification of the amount of Internet use by conceiving it as one of the main tools in academic activities; the presence of very flexible study and work schedules among university students; and the existence of low control and supervision of students' Internet activities by parents or legal guardians [17]. Although there are several studies on problematic Internet use that investigate university students [17,25,26], there is little research that focuses on university students who will be future teachers, educators, or social workers [29].…”
Section: Introductionmentioning
confidence: 99%